The politics of Switzerland continuity and change in a consensus democracy - Kriesi, Hanspeter 1949-; Trechsel, Alexander 1971- (Cambridge Univ. Press, 2008)
Despite Switzerland's small size, its political system is one of the most complex and fascinating among contemporary democracies. By focusing on its intricacies but also taking in broader issues of general interest, the broad scope of this study will appeal to all those interested in contemporary European politics.
Includes bibliographical references and index
Keywords: Politieke stelsels; Politik; Demokratie; Direkte Demokratie; Politisches System; Zwitserland; Schweiz; Switzerland -- Politics and government -- 21st century